Ex-Combatants, Religion, and Peace in Northern Ireland - Brewer, J. author. aut Link
XIV, 192 p.
Keywords: Studies of Northern Ireland's ex-combatants ignore religion, while advocates of religious interventions in transitional justice exaggerate its influence. Using interview data with ex-combatants, this book explores religious influences upon violence and peace, and develops a model for evaluating the role of religion in transitional justice.